Synthesis, antiproliferative activity targeting lung cancer and in silico studies of hydroxypiperidine substituted thiosemicarbazones - Aftab, Hina; Islam, Muhammad Shahazul; Şenol, Halil; Batool, Zahra; Ateşoğlu, Şeyma; Çakır, Furkan; Akbaş, Fahri (Nature Research, 2025)
This study focuses on the synthesis, characterization, and evaluation of 13 novel hydroxypiperidine-substituted thiosemicarbazone derivatives (5a-m) for their anticancer activity and enzyme inhibition properties. The compounds were tested for cytotoxicity against A549 lung cancer and BEAS2B non-cancerous cells, with compound 5f (R = 2,3-dichlorophenyl) demonstrating the lowest IC50 value of 0.58 µM and high selectivity (SI = 28.9) for A549 cells. Enzyme inhibition assays revealed that 5f exhibited potent inhibition against human carbonic anhydrase isoforms hCA I and hCA II, with the lowest IC50 and Ki values. Molecular docking studies showed that 5f had the best binding affinity across multiple targets, including hCA isoforms, VEGFR-2, and BRAF, further supported by favorable MM-GBSA binding free energy calculations. Additionally, molecular dynamics simulations confirmed the stability and key interactions in the 5f-protein complexes. ADMET predictions indicated that 5f has favorable drug-likeness and low organ toxicity risk, showing good permeability and oral absorption potential. These findings suggest that 5f is a promising lead compound for further development as a multi-target therapeutic agent for lung cancer. © 2025 Elsevier B.V., All rights reserved.
Keywords: Carbonic Anhydrase; Lung Cancer; Molecular Docking; Molecular Dynamics; Thiosemicarbazone